STATUS POPULASI BUAYA Crocolylus porosus DI DAERAH KAIMANA DAN TELUK ARGUNI IRIAN JAYA - Hellen Kurniati; Yunus Rumbarar; Mumpuni; Gono Semiadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1999)
The people of Indonesia have historically used crocodiles for a variety of non-commercial purposes. In the past ten years, a commercial collection from the wild almost threatened the population status. As pressure on the commercial hunting continuous, the successful conservation of Indonesian crocodiles will depend on the constant monitoring in the wild. Irian Jaya is one of several islands in Indonesia which historically accommodate an unknown number of commercial crocodiles such as Crocolylus porosus. Althorough monitoring on the C. porosus status in Barusam Gasawi, Buruai Garawa, Kamabu rivers, and Suwiki lake located in Kaimana and Arguni Bay, Irian Jaya had been conducted since 1990 and continued in 1991, 1992, 1993, 1994, 1996, and 1998. The surveys techniques were conducted night count method and guided by a 1: 100.000 map and GPS. A statistical analysis was performed on SAS using proc regression and proc mean. A significant result has only been noted in Suwiki Lake, where was the magnitude of the mean trend in density was 109%.